Korelasi Kadar Air pada Kernel terhadap Mutu Kadar Asam Lemak Bebas Produk Palm Kernel Oil yang Dihasilkan - Azhar Basyir Rantawi (Politeknik Kelapa Sawit Citra Widya Edukasi, 2021)
The quality of Palm Kernel Oil (PKO) is influenced by the quality of the kernel to be processed. Meanwhile, the quality of the kernel is influenced by the temperature and duration time of drying. The purpose of this research was to determine the correlation between moisture content in the kernel and free fatty acid content in PKO. The research was conducted at PT XYZ. The method used to determine the moisture content in the kernel is drying using a microwave, while to determine the free fatty acid content in PKO is using titration. Data analysis method used is correlation analysis. The result showed that there was not a significant influence between the moisture content in the kernel and the free fatty acid content in PKO, so that if the moisture content in the kernel was higher, the free fatty acid content in PKO would not always be higher.